Pemanfaatan LNG sebagai Bahan Bakar Kendaraan Umum di Yogyakarta: Tinjauan Aspek Keselamatan dalam Pengangkutan dan Penyimpanan - Didik Supriyadi; Moh. Mahrurrozi; Indra Perdana (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Liquefied natural gas (LNG) has economic and technical benefits as an alternative fuel for public transportation and heavy-duty vehicle. It is also safer, more reliable and more secure from domestic energy supply. However, LNG possesses different hazard compared to conventional automotive fuel. This paper aims to discuss about risk analysis on LNG transportation and storage as part of an energy supply system for public transportation in Yogyakarta city. This study was conducted for transportation routes between receiving terminal in Semarang port and storage facility in Yogyakarta. Storage capacity was assumed to serve for 12-day-operation which is equivalent to three storages with a capacity of 53 m3 each. The results of risk analysis show that the causes of LNG release were failure of loading LNG to road tank and unloading to storage facility with frequency of 2,4 x10-3failures/year and 7,4 x 10-5 failures/year respectively. The study also found the most probable outcomes that give significant consequences were pool fire, fire ball, vapor cloud explosion and vapor cloud. These results have led to the conclusion that LNG transportation and storage to support public transportation in Yogyakarta city is safe and reliable as long as a good standard operation procedure is consistently implemented